Perancangan Affiliate Guidelines Berbasis Design Thinking guna Meminimalisasi Misleading Claim pada Konten Pemasaran Suplemen Kesehatan - Risa Ardila Salamah; Btari Mariska Purwaamijaya; Muhammad Dzikri Ar Ridlo (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
The rapid growth of TikTok affiliate marketing has increased the promotion of health supplement products through short-form digital content. However, many affiliates still lack sufficient understanding of health claim regulations, leading to misleading promotional statements that may harm consumer trust and violate regulatory standards. This study aims to develop affiliate guidelines that help affiliates create promotional content that is both engaging and compliant with health supplement advertising regulations. The research employed a Research and Development (R&D) approach using the design thinking model, which includes the stages of empathize, define, ideate, prototype, and test. Data were collected through observations, semi-structured interviews, and documentation involving three affiliates and two merchant representatives of ERHA Herbal. The study resulted in an affiliate guideline in the form of an e-book containing claim limitations, safe promotional language, content checklists, and practical content examples. Product validation showed highly valid results, with scores of 92.5% from design experts and 85.71% from material experts. The findings indicate that the developed guideline can assist affiliates in producing more responsible, accurate, and regulation-compliant marketing content on TikTok.